Heads-Up: Risk-Specific Neurodegenerative Mortality and Years-Saved Analysis on the US Olympian Cohort - Yamazaki, Moi; De Larochelambert, Quentin; Sauliere, Guillaume; Toussaint, Jean-François; Antero, Juliana (Frontiers in Physiology, 2021)
Purpose: To identify the risk of neurodegenerative death (ND) that former elite athletes endure Purpose: To identify the risk of neurodegenerative death (ND) that former Olympians endure according to participation in sports grouped based on presumed repeated shocks to the head, and to understand the impact of such elite sport participation on their total longevity. Methods: The cohort included all former US Olympians, who participated in the Olympic Games between 1948 and 1972, and whose vital statuses and causes of death were verified (n = 2193). Olympic sports were classified in three categories of exposure: Collision (the highest presumed risk of repeated shocks to the head), Contact, and No-contact. Fine-Gray competing risk regression model was used to compare the risk of ND where No-contact was a reference group. Years-saved analysis was performed to quantify the number of years saved or lost to ND and total longevity compared to the US general population. Results: 65 NDs were identified. Collision sports Olympians had 3.11 (CI95: 1.31 to 7.40) higher risk of ND while the Contact group showed a risk of 0.56 (CI95: 0.21 to1.48) compared to No-Contact sports Olympians. Compared to the general population, Collision group lost 0.61 (CI95: -1.16 to -0.06) years of life from ND, while Contact group saved 0.4 (CI95: 0.26 to 0.54) and No-contact group saved 0.09 (-0.09 to 0.28) year of life up to the age of 90. Regarding the total longevity, Collision, Contact and No-contact groups saved 4.67 (CI95: 3.13 – 6. 22), 5.8 (CI 95: 4.93 – 6.67) and 6.24 (CI 95: 5.57 – 6.92) years of life respectively from all causes of death. Conclusion: There is an elevated risk of ND among US Olympians who engaged in the sports with the highest presumed risk of repeated shocks to the head compared to those exposed to no such hazard. Such risk does not jeopardize the total longevity among Olympians in Collision sports. (300 words)